2010
DOI: 10.1093/abbs/gmq089
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation inhibits neointimal hyperplasia after abdominal aorta balloon injury through the PTEN/p27Kip1 pathway

Abstract: Electric fields (EFs) exert biological effects on promoting wound healing by facilitating cell division, cell proliferation, and cell directional migration toward the wound. In this study, we examined the inhibitory effect of directcurrent (DC) EFs on the formation of neointimal hyperplasia and the possible mechanism in an abdominal aorta balloon injury rabbit model. Sixty rabbits were divided into normal, control, and experimental groups. After establishment of the abdominal aorta balloon injury model, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…More likely, the difference in restenosis may be explained by induction of the cyclin-dependent kinase inhibitor p27 Kip1 . Stents loaded with 300 μg 6-MP showed increased p27 Kip1 expression in intimal SMC, in accordance with previous studies showing the relation between p27 Kip1 and neointima hyperplasia [ 32 , 33 ], and between p27 Kip1 and 6-MP or Nur77 [ 15 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…More likely, the difference in restenosis may be explained by induction of the cyclin-dependent kinase inhibitor p27 Kip1 . Stents loaded with 300 μg 6-MP showed increased p27 Kip1 expression in intimal SMC, in accordance with previous studies showing the relation between p27 Kip1 and neointima hyperplasia [ 32 , 33 ], and between p27 Kip1 and 6-MP or Nur77 [ 15 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…There are reports demonstrating that ES on a range of cell types reduced cell proliferation (Hernandez‐Bule et al, ; Oshima et al, , ; Sebastian et al, ; Thrivikraman et al, ; Wang et al, ; Zhang et al, ). Several mechanisms initiated by ES which inhibit cell proliferation include cell cycle arrest, intracellular Ca 2+ influx and upregulation of tumor suppressor proteins.…”
Section: The Effects Of Es On Cell Proliferationmentioning
confidence: 99%
“…Despite reports on the effects of ES inducing either increased or decreased cell apoptosis, several studies showed that ES resulted in no effect on cell apoptosis (Huang et al, ; Linkov et al, ; Pedrotty et al, ; Qi et al, ; Sebastian et al, ; Thrivikraman, Madras, & Basu, ; Zhang et al, ). These reports are summarized in Table .…”
Section: The Effects Of Es On Cell Apoptosismentioning
confidence: 99%
See 2 more Smart Citations